Effect of Dietary Utilization of Cassava Root (Monihot esculenta) Meal on Growth Performance and Carcass Characteristics of Broiler Chickens at Finisher Phase - Tamburawa, M. S.; Abubakar, Z.; Salisu, N.; Wudil, A. A.; Hassan, A. M.; Ibrahim, U.; Zango, M.H.; Nasir, M.; Umar, A. M.; Sa’idu, S. S. (Nigerian Journal of Animal Science and Technology (NJAST), 2019)
This study was conducted to determine the growth performance and carcass characteristics of broiler chickens fed diets containing Cassava Roots Meal (CRM) at finisher phase. A total of ninety (90) four weeks old broiler chicks (Marshal Strain) were used for the study. Five experimental diets were formulated and fed to broiler chickens at dietary levels of 0, 15, 30, 45 and 60% represented as T1, T2, T3, T4 and T5, respectively. The experimental design was a Completely Randomized Design (CRD) and each treatment was replicated 3 times with 6 birds per replicate. The experiment lasted 4 weeks. Data were collected on performance and carcass characteristics. The results of performance showed there were significant differences (P < 0.05) in the final body weight (2083.33-2463.33 g), daily weight gain (55.56-68.27 g) feed conversion ratio, (2.70-3.34) and feed cost/kg gain.(N208.04- 240.09). However, there were no significant differences (P > 0.05) in the initial body weight, daily feed intake and mortality rate. The carcass yields were significantly (p<0.05) affected by dietary inclusion in the final live weight (2083-2463 g), carcass weight (1377.00 -1715.00 g), thigh muscle (141.33-228.00 g), back weight (367.67 - 493.33 g) and dressing percentage (62.44 - 69.61%). The final live weight and dressing percentage were highest in broiler chickens fed T4 (45 % cassava root meal diets). There were significant differences (P<0.05) in proventriculus, gizzard and kidney weights. There were no significant differences (P > 0.05) in liver, heart, lung, spleen and pancreas weights. It was observed that broiler chickens at finisher phase performed better and gave higher values of carcass characteistics at 45% (cassava root meal diet) compared to other treatments. Based on the results of this study, it was concluded that cassava root meal can replace maize up to 45% without any deleterious effect on the growth performance, carcass yield and organs weights of broilers with some reduction in the cost of production.